Evidences of Construct Validity of the NEUPSILIN Using Confirmatory Factorial Analysis - Pawlowski, Josiane (2014)
The objective was to provide evidences of construct validity of the NEUPSILIN Brief Neuropsychological Assessment Instrument. The participants were 1017 healthy Brazilian, 67.1% women, 12 to 90 years old (M = 36.72; SD = 23.90) and 1-27 years of education (M = 8.68; SD = 4.02). Participants answered the 32 tasks of NEUPSILIN that assess orientation, attention, perception, memory, arithmetic abilities, language, praxis and executive functions. Theoretical-hypothetical, adjusted and alternative models of language, memory, praxis and executive functions were analyzed with Generalized Least Square method of AMOS (18.0). The adjusted models of language and praxis, the hypothetical-theoretical model of verbal memory and the alternative model of executive functions showed better adjustment indicators than other models. Results indicate the validity of measures of language, memory, praxis and executive functions of NEUPSILIN.